Natural Antioxidants and Biocides from Wild Medicinal Plants - Cespedes, C. L.; Rai, Mahendra; Sampietro, Diego A.; Seigler, David S.; Ebooks Corporation (Wallingford : CABI, 2013)
This title offers up-to-date knowledge on antioxidant and biocidal compounds from plants in a single source. Plants produce secondary metabolites with herbicidal, insecticidal, fungicidal and antioxidant activities, which offer alternatives for the control of pests and diseases, and in some cases directly contribute to improving food quality. It offers a comprehensive general overview and perspective on antioxidant, medicinal and biocidal plant compounds, isolated from a wide range of species, mainly from Latin America. For the first time information on new antimicrobials, insecticidals, and antioxidants are compiled in a single source. It is based on the research and knowledge of several internationally renowned research groups. It is an invaluable reference for students, researchers and teachers interested in allelochemistry as well as the antioxidant and medicinal properties of Latin American Plants. It is unique in its coverage of biocides from wild plants. It is suitable for students, researchers and teachers interested in biopesticidal, biocidal, allelochemistry, antioxidant and agrochemical and medicinal properties.It is also useful for drugs manufacturers, particularly those who deal with herbal preparations.
Contenido: 8 Chilean Plants as a source of Polyphenols9 Antioxidant Activity of Anacardic Acids; PART III. BIOCIDAL ACTIVITIES; 10 Alkylresorcinols: Chemical Properties, Methods of Analysis and Potential Uses in Food, Industry and Plant Protection; 11 Phytoecdysteroids and Related Sterols Isolated from Mexican Cacti: their Potential Use as Natural Insecticides; 12 Zuccagnia punctata Cav
Libro electronico adquirido a perpetuidad con la editorial CABI
Keywords: ANTIOXIDANTES; CONTROL BIOLOGICO DE PLAGAS; METABOLITOS VEGETALES; PLANTAS MEDICINALES; QUIMICA VEGETAL